Acidosis Induced Disseminated Intravascular Microthrombosis and its Dissolution by Streptokinase - Broersma, R. J; Bullemer, G. D; Mammen, E. F (Thrombosis and Haemostasis, 1970)
To elucidate the mechanisms triggering disseminated intravascular coagulation (DIC) in shock, acidosis was produced in dogs by intravenous infusions of lactic acid over a period of 4 h. As the pH of the blood dropped, the blood pressure increased and the heart rate fell. The platelet counts dropped and whole blood clotting times shortened. The partial thromboplastin times and prothrombin times decreased as did the r-times and maximal amplitudes of the thrombelastograms. Simultaneously, the levels of prothrombin, fibrinogen, factors V and VIII decreased with time in acidosis. There was no evidence of a systemic activation of the fibrinolytic system. The euglobulin lysis times increased as did the thrombin times and there was no lysis observed in the thrombelastograms.Thrombi in the lungs, liver, spleen and kidneys, together with the coagulation changes indicated that the infusion of acid produced DIC, with the changes being similar to those produced in shock. The glomeruli were especially affected and the pictures were identical to those described in kidneys of animals having experienced a generalized Sanarelli-Shwartzman phenomenon.A pH value of 7.20 or lower appeared to be a potent trigger of intravascular coagulation. The lower the pH, the more thrombi were found in the tissues. The consumption of clotting factors and thrombus formation thus corresponded to the degree of acidosis.A generalized fibrinolytic state was induced using Streptokinase, after a 4 h period of acidosis and 1 h of compensation with sodium bicarbonate. Streptokinase was infused along with human euglobulin fractions on the basis of the streptokinase tolerance test of each dog’s blood and plasma. Thrombolysis was maintained for 3-4 h and this was reflected in the reduction of fibrin deposits in the tissues. Of 100 glomeruli counted/dog’s kidney, the average containing fibrin was 44 ± 11% after acidosis and 0.4 ± 0.3% after thrombolysis.